Gloss on the resolution of a panel of seven judges of the Supreme Administrative Court of 21 November 2021, I OPS 2/21 (Ius Novum, 2022)
The subject of the gloss is a resolution of the Supreme Administrative Court in which theCourt examined the rules of determining income in social assistance proceedings. Whilerecognising the possibility of reducing income solely by the amount of alimony provided toan entitled person under the provisions of the family and guardianship code, the SupremeAdministrative Court stated unequivocally that the privileged method of determining incomecannot be used by persons who do not pay alimony and are obliged to make payments to thealimony fund. This gloss presents arguments supporting the theses contained in the resolutionand their axiological justification. Moreover, it elaborates on the issues indirectly raised by theadjudicating panel, such as overdue alimony and amounts that are actually paid as part ofalimony. This subject is important for determining the income of persons applying for supportunder the social assistance system as well as paying for benefits.
Keywords: alimony; alimony fund; social assistance